Selected Decisions and Selected Documents of the International Monetary Fund, 33rd Issue. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This volume is the Thirty-Third Issue of "Selected Decisions and Selected Documents of the International Monetary Fund." It includes decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the International Monetary Fund, as well selected documents, to which frequent reference is made in the current activities of the Fund. In addition, it includes certain documents relating to the Fund, the United States, and other international organizations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet